Pengaruh Disliplin Kerja Guru dan Kepemimpinan Kepala Sekolah terhadap Kinerja Guru - Aman , Muhamad; Fitria , Happy; Fitriani , Yessi (Yayasan Darusssalam Bengkulu, 2020)
This study aims to: (1) identify and describe the effect of teacher work discipline on teacher performance; (2) knowing and describing whether there is an influence of the principal's leadership on performance, and (3) knowing and describing whether there is an effect of discipline and leadership of the principal on teacher performance. This research uses quantitative methods. The population of this research is the principal and teachers of SD Negeri Batanghari Leko Regency. Data collection techniques are questionnaires, observation, and documentation. The results of the calculation of the stimulus comparing the table test and the fcount test between the variables X1 (certification), X2 (principal leadership) and the variable Y (performance), obtained a value of 52,329> 3.21 in the value of the table. This very large difference in value certainly means that the two independent variables (X1 and X2) together have a positive and significant effect on the dependent variable (Y).